2012
DOI: 10.3324/haematol.2012.063172
|View full text |Cite
|
Sign up to set email alerts
|

Has the time for first-line treatment with second generation tyrosine kinase inhibitors in patients with chronic myelogenous leukemia already come? Systematic review and meta-analysis

Abstract: ARTICLES 95Chronic myeloid leukemia Second generation tyrosine kinase inhibitors have recently been introduced as first-line treatment for chronic phase chronic myelogenous leukemia. We aimed to evaluate the efficacy and safety of 2 nd generation tyrosine kinase inhibitors versus imatinib as first-line treatment for these patients. We carried out a systematic review and meta-analysis of randomized controlled trials comparing 2 nd generation tyrosine kinase inhibitors to imatinib as first-line treatment in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…One point is the choice of the first TKI. [162][163][164] Two trials have shown an initial superiority of second-generation TKIs vs imatinib, with significant differences in response but not yet in outcome. [9][10][11][12][13] They justify placing nilotinib and dasatinib in the front-line setting but do not justify the exclusion of imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…One point is the choice of the first TKI. [162][163][164] Two trials have shown an initial superiority of second-generation TKIs vs imatinib, with significant differences in response but not yet in outcome. [9][10][11][12][13] They justify placing nilotinib and dasatinib in the front-line setting but do not justify the exclusion of imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve and to maintain these goals, it is possible to choose among several TKIs, and a chronic, lifelong treatment is required. However, the scenario is changing, the goal is moving from survival to cure, and the treatment policies are moving towards discontinuation [1,6,7,[56][57][58]. The next goal is to achieve a condition of treatmentfree remission (TFR) [59][60][61].…”
Section: Management Of CML Evolution Of Goals and Strategiesmentioning
confidence: 97%
“…The overall pooled OR and 95% CI were estimated using the Mantel-Haenszel method with a fixed-effect model when no significant clinical or statistical heterogeneity was pres-ent (P ≥ 0.10) (Gurion et al, 2013). When substantial heterogeneity was present, the randomeffect model was used.…”
Section: Discussionmentioning
confidence: 99%